2016
DOI: 10.1080/08870446.2015.1117082
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized goal framing: How health messages are influenced by valence and contextual/analytic processing

Abstract: The effectiveness of health messages has been shown to vary due to the positive or negative framing of information, often known as goal framing. In two experiments we altered, the strength of the goal framing manipulation by selectively activating the processing style of the left or right hemisphere (RH). In Experiment 1, we found support for the contextual/analytic perspective; a significant goal framing effect was observed when the contextual processing style of the RH - but not the analytic processing style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This should result in a message framing effect under conditions of both left as well as right hemisphere activation. Consistent with this prediction, McCormick and Seta (), using a message framing manipulation, reported an advantage for gain‐framed messages under conditions of left hemisphere activation for a message promoting HPV vaccination among participants who had not been vaccinated but were currently in a sexual relationship; the typical advantage for loss‐framed messages was found when right hemisphere processing was initially activated.…”
Section: Matching Effectsmentioning
confidence: 78%
See 2 more Smart Citations
“…This should result in a message framing effect under conditions of both left as well as right hemisphere activation. Consistent with this prediction, McCormick and Seta (), using a message framing manipulation, reported an advantage for gain‐framed messages under conditions of left hemisphere activation for a message promoting HPV vaccination among participants who had not been vaccinated but were currently in a sexual relationship; the typical advantage for loss‐framed messages was found when right hemisphere processing was initially activated.…”
Section: Matching Effectsmentioning
confidence: 78%
“…Furthermore, although FTT explains why responses to framing manipulations are affected by differences between gist and verbatim processing, it does not address findings that go beyond differences in gist and verbatim processing. With the risky choice framing manipulation, for example, responses have been shown to be affected by the match between frame/message‐target characteristics (e.g., valence) as well as the match between perceivers' sensitivity to these characteristics (e.g., McCormick & Seta, ; McElroy, Seta, & Waring, ). FTT does not predict these results.…”
Section: Fuzzy‐trace Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that typical framing effects are often more likely for individuals who process information with a holistic/contextual than an analytic style and for those who do not process the information very elaborately (with a System 1 compared with the more elaborative processing style of System 2; (e.g., Jasper, Fournier, & Christman, ; Kahneman, ; McCormick & Seta, ; McElroy & Seta, ; Murch & Krawczyk, ; Seta et al, ). According to the unification model, this is the case because perceivers who process with a holistic/contextual or System 1 processing style are especially likely to include the psychological implications of the frame into their cognitive representation of the judgmental target and less likely to expand the meaning of the message by including unintended implications, such as information that is in opposition with the frame's meaning.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that typical framing effects are often more likely for individuals who process information with a holistic/contextual than an analytic style and for those who do not process the information very elaborately (with a System 1 compared with the more elaborative processing style of System 2; (e.g., Jasper, Fournier, & Christman, 2014;Kahneman, 2011;McCormick & Seta, 2016;McElroy & Seta, 2004;Murch & Krawczyk, 2014;Seta et al, 2010).…”
Section: System 1 Versus 2 and Analytic/holistic Processingmentioning
confidence: 99%